2010
DOI: 10.3928/01477447-20100329-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Posterior Dynamic and Posterior Rigid Transpedicular Stabilization With Fusion to Treat Degenerative Spondylolisthesis

Abstract: This article describes the clinical and radiological outcomes of a comparison of posterior dynamic transpedicular stabilization and posterior rigid transpedicular stabilization with fusion after decompression in the treatment of degenerative spondylolisthesis. This prospective clinical and radiologic study was conducted between 2004 and 2007 and included 46 patients, of whom 33 were women (71.7%) and 13 were men (28.3%). Mean patient age was 61.67+/-10.80 years (range, 45-89 years). Twenty-six patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
1
26
0
3
Order By: Relevance
“…inclusion criteria (2,3,6,(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(26)(27)(28)(29)(30)33,34,36,37,(41)(42)(43)(45)(46)(47) (Figure 1). For the possible duplicate studies (31&40,14&23,13&15), only the data from the trial with the longest follow-up were used for estimating the incidence of ASD.…”
Section: Zhou Zj Et Al: Can Posterior Dynamic Stabilization Reduce Tmentioning
confidence: 99%
See 1 more Smart Citation
“…inclusion criteria (2,3,6,(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(26)(27)(28)(29)(30)33,34,36,37,(41)(42)(43)(45)(46)(47) (Figure 1). For the possible duplicate studies (31&40,14&23,13&15), only the data from the trial with the longest follow-up were used for estimating the incidence of ASD.…”
Section: Zhou Zj Et Al: Can Posterior Dynamic Stabilization Reduce Tmentioning
confidence: 99%
“…Among the 23 articles with the PDS procedure only, twelve reported the incidence of ASDeg (Table I), and thirteen reported that of ASDis (Table II), with two articles investigating both rates. Four investigations compared the incidence of ASDeg/ASDis between the PDS and fusion procedures (13,16,17,29).…”
Section: Zhou Zj Et Al: Can Posterior Dynamic Stabilization Reduce Tmentioning
confidence: 99%
“…Seven studies in this analysis included patients with spondylolisthesis (Grade I). Although the rates of spondylolisthesis were 49% and 100% in the reports by Kaner et al 13 and Yu et al, 39 the Dynesys groups in these studies had similar clinical and radiological outcomes that were not inferior to those of the PLIF groups. Previous reports also found that Dynesys provides similar radiographic stability and clinical effects regardless of preoperative spondylolisthesis.…”
Section: Evaluation Of Possible Disadvantages Of the Dynesys Systemmentioning
confidence: 61%
“…9,38 Among the 7 studies, Kaner et al 13 included patients with Grade I or II spondylolisthesis, and the others included patients with only Grade I spondylolisthesis.…”
Section: Risk Of Bias Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation